A Helminth-Derived Chitinase Structurally Similar to Mammalian Chitinase Displays Immunomodulatory Properties in Inflammatory Lung Disease - Friederike Ebner; Katja Lindner; Katharina Janek; Agathe Niewienda; Piotr H. Malecki; Manfred S. Weiss; Tara E. Sutherland; Arnd Heuser; Anja A. Kühl; Jürgen Zentek; Andreas Hofmann; Susanne Hartmann (Journal of Immunology Research)
Immunomodulation of airway hyperreactivity by excretory-secretory (ES) products of the first larval stage (L1) of the gastrointestinal nematode Trichuris suis is reported by us and others. Here, we aimed to identify the proteins accounting for the modulatory effects of the T. suis L1 ES proteins and studied six selected T. suis L1 proteins for their immunomodulatory efficacy in a murine OVA-induced allergic airway disease model. In particular, an enzymatically active T. suis chitinase mediated amelioration of clinical signs of airway hyperreactivity, primarily associated with suppression of eosinophil recruitment into the lung, the associated chemokines, and increased numbers of RELMα+ interstitial lung macrophages. While there is no indication of T. suis chitinase directly interfering with dendritic cell activation or antigen presentation to CD4 T cells, treatment of allergic mice with the worm chitinase influenced the hosts’ own chitinase activity in the inflamed lung. The three-dimensional structure of the T. suis chitinase as determined by high-resolution X-ray crystallography revealed high similarities to mouse acidic mammalian chitinase (AMCase) but a unique ability of T. suis chitinase to form dimers. Our data indicate that the structural similarities between the parasite and host chitinase contribute to the disease-ameliorating effect of the helminth-derived chitinase on allergic lung inflammation.